CHANGES IN THE MARKERS OF CARBOHYDRATE METABOLISM DURING ANTI-TUBERCULOSIS THERAPY IN TUBERCULOSIS PATIENTS WITH CONCURRENT DIABETES - R. Yu. Abdullaev; O. G. Komissarova; O. O. Bobina; S. V. Aleshina; A. E. Ergeshov (Туберкулез и болезни лёгких)
The objective of the study: to study markers of carbohydrate metabolism in pulmonary tuberculosis patients with concurrent diabetes during treatment of tuberculosis.Subjects and methods. 156 pulmonary tuberculosis patients, divided into 2 groups, were examined. Group 1 included 69 (44.2%) pulmonary tuberculosis patients with concurrent type 1 diabetes. Group 2 included 87 (55.8%) pulmonary tuberculosis patients with concurrent type 2 diabetes.Results. Prior to the start of anti-tuberculosis treatment, disorders of carbohydrate metabolism in type 1 diabetes patients were more expressed: there were the statistically significant higher level of glycated hemoglobin and glucosuria severity during the daytime (within 8-14 hour interval). Analysis of changes in carbohydrate metabolism markers showed that there was a gradual trend for their improvement if the treatment was effective and should treatment be failing, the disorders of carbohydrate metabolism were deteriorating.Conclusion. Tuberculosis deteriorated the severity of diabetes, especially of type 1, compromising the efficacy of antihyperglycemic therapy. A significant part of treatment failures among type 1 diabetes patients was potentially associated with the negative impact of poorly compensated diabetes.